2017
DOI: 10.36487/acg_rep/1704_25_sjoberg
|View full text |Cite
|
Sign up to set email alerts
|

Deep sublevel cave mining and surface influence

Abstract: With increasing mining depths and excavation volumes comes not only increased rock stresses and more difficult underground mining conditions, but also increased surface effects, in particular from cave mining. The surface effects of deep sublevel cave mining are not well understood and are further explored in this paper, through a case study of the LKAB Kiirunavaara Mine. Two different numerical modelling approaches were used to quantify potential surface effects. The first approach was applied to Sjömalmen (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In this work, only historical mining was simulated. The methodology was re-applied, with refined calibration against cratering observations and then model validation using deformations measurement data, followed by simulation of future mining (Sjöberg et al 2017). The modelling results showed that the extent of the zone of mining-induced deformations on the ground surface increased significantly with future mining at depth (Figure 11), continuing in more-or-less the same fashion as historically, when mining continues for another 300-400 m towards depth.…”
Section: Advances In Modelling Of Cavingmentioning
confidence: 99%
“…In this work, only historical mining was simulated. The methodology was re-applied, with refined calibration against cratering observations and then model validation using deformations measurement data, followed by simulation of future mining (Sjöberg et al 2017). The modelling results showed that the extent of the zone of mining-induced deformations on the ground surface increased significantly with future mining at depth (Figure 11), continuing in more-or-less the same fashion as historically, when mining continues for another 300-400 m towards depth.…”
Section: Advances In Modelling Of Cavingmentioning
confidence: 99%
“…Ideally, one would model this process using a pure discontinuum approach with explicit breakage of rock blocks. However, the computational size and time requirements to solve mine-scale problems make it currently impossible to tackle the problem completely with the discontinuum approach (Sjöberg et al 2017). Instead, an algorithm to simulate caving has been developed within the concept of a continuum-based model.…”
Section: Modelling Approachmentioning
confidence: 99%